Roads Economic Decision Model (RED) Economic Evaluation of Low Volume Roads - Archondo-Callao, Rodrigo S. (2012)
This note presents the Roads Economic Decision Model (RED) that performs an economic evaluation of road investments, and maintenance options, customized to the characteristics of low-volume roads, such as: high uncertainty of the assessment of traffic, road condition, and future maintenance of unpaved roads; periods with pass disruptions; levels of service, and corresponding road user costs defined not only through roughness; high potential to influence economic development; and, beneficiaries, other than motorized road users. The model computes benefits accruing to normal, generated, and diverted traffic, as a function of a reduction in vehicle operating, and time costs, and, adopts the consumer surplus approach, which measures the benefits of road users, and consumers of reduced transport costs. RED addresses, among others, the following additional concerns: reduce input requirements for low-volume roads; consider the higher uncertainty, related to input requirements; compute internally the traffic generated due to decreased transport costs, based on a defined price elasticity of demand; and, quantify the economic costs, associated with the days per year when the passage of vehicles is further disrupted by a highly deteriorated road condition. Particularly, the model highlights all input assumptions, and comprehensively integrates them with sensitivity, switching values, and stochastic risk analysis.